2002
DOI: 10.1007/bf02465600
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and body temperature in the Griffon Vulture (Gyps fulvus) with comparative data on the Hooded Vulture (Necrosyrtes monachus) and the White-backed Vulture (Gyps africanus)

Abstract: The diurnal cycle of metabolic rate (MR, J/g.h, based on Vo2 and Vco2) was measured in 14 Griffon Vultures (Gypsfulvus), two Hooded Vultures (Necrosyrtes monachus) and one White-backed Vulture (Gyps africanus) at different ambient temperatures (-7 to +34 °C).In (so far) three Griffon Vultures the heart rate (HR) and body temperature (Tb) were measured by telemetry, simultaneously with MR. The three vulture species show very similar physiological mechanisms. In all cases measured MR is significantly below allom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…These results suggested a decrease in the capacity to cope with intra‐seasonal changes in temperature. Within their natural environment, griffon vultures are exposed to both high temperatures in southern Europe and the Middle East and to low temperatures during flight at high altitudes and have developed metabolic and physiological adaptations to harsh climatic conditions (Prinzinger et al ). Therefore, in adult individuals, meteorological conditions at the Causses study site are not expected to greatly affect survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested a decrease in the capacity to cope with intra‐seasonal changes in temperature. Within their natural environment, griffon vultures are exposed to both high temperatures in southern Europe and the Middle East and to low temperatures during flight at high altitudes and have developed metabolic and physiological adaptations to harsh climatic conditions (Prinzinger et al ). Therefore, in adult individuals, meteorological conditions at the Causses study site are not expected to greatly affect survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in adult individuals, meteorological conditions at the Causses study site are not expected to greatly affect survival. To cope with changes in ambient temperature and limit the expenditure of energy, the body temperature of griffon vultures increases or decreases in relation to the ambient temperature, which buffers their metabolic rate over a large temperature range (Bahat et al , Prinzinger et al ). We hypothesize that metabolism degradation due to senescence may reduce the effectiveness of this regulation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, once our knowledge about applying accelerometers improves, the high‐resolution time and energy data they will likely provide will be valuable for comparative studies between bird species (Prinzinger et al 2002, Zahedi and Khan 2007). Furthermore, such data may be useful for conservation physiologists (Wikelski and Cooke 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Vultures are large obligate scavengers that rely on thermal and orographic uplift for their soaring flight that enables them to cover long distances in search of carcasses [ 21 ]. Because carcasses are an irregular and unpredictable resource, vultures frequently experience long intervals between successive feedings and are adapted to cope with fasting periods of up to two weeks without detrimental effects [ 22 , 23 ]. Field studies have shown that griffon vultures ( Gyps fulvus ) regularly fast for several days between successive meals.…”
Section: Introductionmentioning
confidence: 99%